EFEK INSTABILITAS NILAI TUKAR RUPIAH TERHADAP PENAWARAN EKSPOR KOPI INDONESIA DAN HARGA KOPI DOMESTIKEFEK INSTABILITAS NILAI TUKAR RUPIAH TERHADAP PENAWARAN EKSPOR KOPI INDONESIA DAN HARGA KOPI DOMESTIKEFEK INSTABILITAS NILAI TUKAR RUPIAH TERHADAP PENAWARAN EKSPOR KOPI INDONESIA DAN HARGA KOPI DOMESTIK - Aprilla, Sandi; Sukiyono, Ketut; Romdhon, M. Mustopa (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2012)
This research is to examine the volatility of rupiah exhange rate and investigate influenced factors to export supply and domestic price of Indonesian Coffee. Double log model of export supply as proposed by Cerra dan Saxena (2003) and of domestic price are used in this study. Using three monthly data of 1990:1 to 2005:4, the result shows that export supply of Indonesian coffee is significantly and positively inflenced by International coffee price and previous export, and negatively influenced by exchange rate instability while domestic price is not. Domestic price is influenced positively by international coffee price, is not by exchange rate instability.